Log-Rank Test on Road Traffic Accident Data in Batu Pahat, Johor, Malaysia - Lai, Jessintha; Abdullah, Mohd Asrul Affendi (Journal of Science and Technology, 2017)
Road traffic accident (RTA) is defined as an accident, which happens on the road between two or more objects, one of which must be any types of a moving vehicle. Nowadays, Malaysia went through rapid growth experienced in the population, economy, and motorization. Therefore,the accidents rates increased every year then become huge threat to public health and national authorities.Batu Pahat is one of the district in the south of Malaysia state, known as Johor that recorded the highest accident rate compared to other district". Thus, this study aims to determine if there are any significant difference on survival of RTA for different years in Batu Pahat district.Besides, this study identified the peak time of road network to determine associated measured could be adopt to reduce the likelihood and severity of accident. The log-rank test has been used to determine the Kaplan-meier curves of RTA for the different year. Data that been used in this study collected from Batu Pahat Police Station. Result shows that three peak times of RTA identified and the log-rank test concluded that there are no significant difference in survival of RTA for different years.